Pigeon rotavirus A genotype G18P[17]-associated disease outbreaks after fancy pigeon shows in Germany – a case series - Schmidt, Volker; Kümpel, Michael; Cramer, Kerstin; Sieg, Michael; Harzer, Maxi; Rückner, Antje; Heenemann, Kristin (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2021)
Objective Pigeon rotavirus A (RVA) isolates of genotype G18P[17] are causing disease outbreaks and fatalities in pigeon lofts in Australia, Germany, Belgium, Denmark and USA since 2016. Most disease outbreaks have been reported from juvenile pigeons (Columba livia forma domestica). However, reports on RVA-associated disease outbreaks in fancy pigeons in connection with fancy pigeon shows in Germany are rare.Material and methods Overall 18 pigeons (16 fancy pigeons and one racing pigeon from 9 pigeon fanciers, as well as one feral pigeon from a rescue center) were sent in for routine diagnostic necropsy including histopathologic, parasitologic and microbiologic examinations. Molecular biologic examinations for detection of RVA, circovirus, Usutu virus, West Nile virus and Chlamydia psittaci were also carried out on all pigeons. An accompanying questionnaire filled in by the senders was used to generate basic information on the affected pigeon lofts.Results Disease outbreaks in juvenile and adult pigeons were reported 7–14 days after fancy pigeon shows. One fancier who had previously vaccinated his pigeons with an autogenous pigeon RVA vaccine, noted no morbidity and mortality among his pigeons and thus sent in a healthy pigeon for diagnostic purposes. Reported clinical signs in the other pigeons were regurgitation, green slimy diarrhea, anorexia, apathy and death after 24 hours. Hepatic necrosis and detection of pigeon RVA isolates of genotype G18P[17] confirmed disease outbreaks caused by pigeon RVA in all pigeons, except for the vaccinated pigeon. Besides pigeon circovirus, which was detected in 15 of 18 pigeons, all other pathogens were singular findings.Conclusion and clinical relevance In disease outbreaks following fancy pigeon shows in juvenile and adult pigeons diagnostics should include pigeon RVA of genotype G18P[17].
Keywords: Avian rotavirus A; RVA; hepatic necrosis; circovirus; PiCV